Science capital and accessible museum practices: applying double lenses in a case study with blind and deaf visitors in the Brazilian context - Heck, Gabriela; Norberto Rocha, Jessica; Bizerra, Alessandra Fernandes; Ferraro, Jose Luis (Frontiers in Education, 2025)
This exploratory and qualitative research aims to investigate how Science Capital is connected with accessibility. The study participants were adults, self-identified as blind or Deaf users of Brazilian Sign Language. They were invited to a guided visit at an exhibition at a science museum in Brazil, where data was collected through interviews, observations, and questionnaires. After conducting a thematic analysis, three main categories emerged: (1) Mechanisms of In/Exclusion in Museums and Science, (2) Scientific Content in Context and (3) Attitudes, Values, and Science-Related Dispositions. In each category, evidence shows correlations between accessibility indicators and dimensions of Science Capital. The results from the Science Capital Index questionnaires revealed changes in all participants' scores, with one of the most significant changes being how participants understood what it means to be a scientist. Our study advances previous research that used the Science Capital model by addressing its limitations when applied to people with disabilities. It also challenges the original British/Eurocentric design by proposing a more inclusive approach that considers structural inequalities and contextual barriers, particularly in the Global South.